Digestibilidade e custo da ração concentrada com níveis Crescentes de ureia em catetos (pecari tajacu) - Camara, Pedro Lucas de Oliveira (2019)
The Pecari tajacu have a digestive physiology of fermentative characterization, which allows the use of non - soluble carbohydrates and nitrogen compounds in their diet, and present a protein requirement of 12 to 14% for growth and termination, respectively. Within this context, the objective was to evaluate alternative sources of protein supplied as urea in the diet of hounds. The experiment was carried out at the Universidade Federal Rural do SemiÁrido, at the scientific breeding center for the Centro de Multiplicação de Animais Silvestres. Twenty adult male animals were submitted to a 15% isoprotein diet; ground corn, soybean meal, wheat bran and mineral supplement; varying the levels of urea in its composition (0%, 1%, 2% and 2.5%). The experimental period lasted 15 days with collections of blood, faeces, urine and feed on day zero (initial) and day 15 (final). The animals were conditioned in individual stalls with feed supplied twice a day with readjustment of leftovers of 20% and supply of water ad libitum. The dry matter (DM), organic matter (OM), mineral matter (MM) and crude protein (CP), determined according to the Association of Official Analytical Chemists (1995). Neutral detergent fiber (NDF) was analyzed according to Van Soest (1991). The coefficients of digestibility (CD) and nitrogen balance (BN) were determined according to the method recommended by Maynard (1984). The economic feasibility of using ration was determined according to the equation proposed by Bellaver et al. (1985) and Fialho et al. (1992). There was no statistical difference for the variable weight gain and digestibility coefficients, however, there was a significant decrease in the dry matter intake when urea level was raised up to 2.5%. Although the animals showed no symptoms of intoxication, there were changes in creatinine levels and total proteins suggesting a slight overload in the kidneys. Considering that the increase in urea inclusion progressively reduced the protein content of the base diet, and that the level of 2.5% employed differ significantly from that obtained for the other experimental groups, it may be recommended to include up to 1% of urea in adult cat litter rations, in addition to being economically viable